Teacher Performance Pay in the United States: Incidence and Adult Outcomes - Timothy N. Bond; Kevin J. Mumford (Institute of Labor Economics (IZA), 2018)
This paper estimates the effect of exposure to teacher pay-for-performance programs on adult outcomes. We construct a comprehensive data set of schools which have implemented teacher performance pay programs across the United States since 1986, and use our data to calculate the fraction of students by race in each grade and in each state who are affected by a teacher performance pay program in a given year. We then calculate the expected years of exposure for each race-specific birth state-grade cohort in the American Community Survey. Cohorts with more exposure are more likely to graduate from high school and earn higher wages as adults. The positive effect is concentrated in grades 1-3 and on programs that targeted schools with a higher fraction of students who are eligible for free and reduced lunch.
Keywords: I24; J24; 330; teacher performance pay; adult outcomes